2015
DOI: 10.17135/jdhs.2015.15.2.113
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Factors Affecting Emotional Labor of Clinical Dental Hygienists

Abstract: This study was conducted to develop a plan for emotional labor of clinical dental hygienists by understanding the factors affecting their emotional labor. Self-administered questionnaires were distributed to 293 dental hygienists who worked in dental hospitals and clinics located in Busan and Gyeongsangnam-do from June to September in 2013. The questionnaire items used in this study consisted of 5 items of general characteristics, 2 items of characteristics related to turnover, and 9 items of emotional labor. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 2 publications
(2 reference statements)
0
3
0
Order By: Relevance
“…The differences in emotional labor according to general characteristics were analyzed, and higher job satisfaction and education level and married marital status led to a significant increase in emotional labor. Kim 12) previously demonstrated that lack of clinical experience, lower or higher salary led to increased emotional labor and Lee et al 13) reported that those who work at dental clinics and have intentions to work at different clinics had higher emotional labor. How does the subject affect emotional labor of dental hygienists is also increased as the size of the hospital increases 4,14) , and increased amount of work and unfair treatment perceived by dental hygienists lead to greater emotional labor 15) .…”
Section: Discussionmentioning
confidence: 99%
“…The differences in emotional labor according to general characteristics were analyzed, and higher job satisfaction and education level and married marital status led to a significant increase in emotional labor. Kim 12) previously demonstrated that lack of clinical experience, lower or higher salary led to increased emotional labor and Lee et al 13) reported that those who work at dental clinics and have intentions to work at different clinics had higher emotional labor. How does the subject affect emotional labor of dental hygienists is also increased as the size of the hospital increases 4,14) , and increased amount of work and unfair treatment perceived by dental hygienists lead to greater emotional labor 15) .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is necessary to prevent and manage stress caused by emotional labor and somatization symptoms arising while dental hygienists are at work. A previous study on the emotional labor of dental hygienists has reported that turnover intention and work organization affect emotional labor in clinical dental hygienists 12) , and the level of dental hygienists' emotional labor is influenced by their personality type 13) . Although many studies have examined the effects of emotional labor on job stress 14) , research on the effects of emotional labor with respect to job stress and somatization among dental hygienists is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Research into the role of emotional labor in job satis-200 faction has been actively conducted. Existing literature encompasses studies on dental hygienists' job satisfaction 7) , emotional labor 8,9) , and job satisfaction according to gender, emotional labor, and intention to quit 10) . Prior research suggests that medical institutions are implementing various strategies to enhance external factors, thereby aiming to increase staff satisfaction and provide an optimal working environment.…”
Section: Introductionmentioning
confidence: 99%